Makna dan Nilai Sosial Tradisi Larung Sesaji di Tasikagung, Rembang - Muhimmatul Alya; Lu'lu' Choirun Nur Fadzillah; Siti Nur Anisah; Nurul Rizqinatul Silvi; Rodhotul Jannah; Dany Miftah M. Nur (Publikasi Inspirasi Indonesia, 2025)
The Larung Sesaji tradition in Tasikagung, Rembang, is a cultural heritage of coastal communities, containing symbolic meaning and social values crucial to community life. The Larung Sesaji tradition holds significant religious, social, and philosophical significance. This ritual not only expresses gratitude for the blessings of the sea but also reflects the harmonious relationship between humans and nature and strengthens coastal community solidarity. Furthermore, this tradition embodies noble values such as character education, mutual cooperation, and social solidarity. Larung Sesaji (offering ceremony) is not merely a traditional ritual; it can serve as an effective learning tool for character building, strengthening unity, and preserving local wisdom amidst modernization. Despite this modernization, this tradition continues and is maintained by the local community to reinforce their identity as a coastal community. Larung Sesaji demonstrates strong solidarity and togetherness through mutual cooperation in preparing the offerings, the procession, and the ceremony. Participatory values are evident in the involvement of various community groups who collectively interpret this tradition as a space to strengthen social ties and maintain local cultural identity. In the context of social studies education, the meaning and social values contained in Larung Sesaji can be used as a contextual learning resource to develop students' understanding of culture, social interaction, and the role of society in preserving tradition. Through the integration of local traditions, students are expected to cultivate tolerance, social awareness, and an appreciation for the nation's cultural heritage. The Larung Sesaji tradition thus serves a crucial role as a medium for shaping community values and character.